2017
DOI: 10.1016/j.micromeso.2017.02.041
|View full text |Cite
|
Sign up to set email alerts
|

High performance of H3BO3 modified USY and equilibrium catalyst with tailored acid sites in catalytic cracking

Abstract: Increasing the cracking ability of catalyst by adjusting its surface acid property is of great significance for oil refining industry. The effects of boric acid on the structure and surface acidity of ultra stabilized Y (USY) and FCC equilibrium catalyst during the modification were investigated. The structural and surface properties of the prepared samples were characterized by low-temperature N 2 sorption, XRD, 27 Al and 29 Si MAS NMR, and FTIR using pyridine probe molecule. Modified USY and equilibrium cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…However, as the crystallinity decreased, the amounts of total acid sites and Lewis acid sites increased slightly at first and then decreased greatly. It indicated that Lewis acid sites, which were found to be the primary source of weak acid sites, were the major acid sites and most of them come from the crystallized zeolites, as previously reported [29,30]. Considering the different operating conditions of NH 3 -TPD and pyridine adsorbed FT-IR analysis, the acid amounts detected were different.…”
Section: Catalytic Tests Of As-synthesized Zsm-5 Catalystssupporting
confidence: 59%
See 1 more Smart Citation
“…However, as the crystallinity decreased, the amounts of total acid sites and Lewis acid sites increased slightly at first and then decreased greatly. It indicated that Lewis acid sites, which were found to be the primary source of weak acid sites, were the major acid sites and most of them come from the crystallized zeolites, as previously reported [29,30]. Considering the different operating conditions of NH 3 -TPD and pyridine adsorbed FT-IR analysis, the acid amounts detected were different.…”
Section: Catalytic Tests Of As-synthesized Zsm-5 Catalystssupporting
confidence: 59%
“…The acid type was further measured by pyridine adsorbed FT-IR spectra, as shown in Figure 7b and Table 3. The bands at 1446 cm −1 and 1549 cm −1 are assigned to the pyridine adsorbed on Lewis acid sites and Brönsted acid sites, respectively [12,[28][29][30]. The bands at 1577 cm −1 and 1596 cm −1 are The strength of accessible acid sites in the selected ZSM-5 catalysts were characterized by NH 3 -TPD tests.…”
Section: Physicochemical Properties Of Zsm-5 Zeolitesmentioning
confidence: 99%
“…Its content gives an idea of the total amount of Al 3+ species, which can be directly correlated with Brønsted-type acidic sites. 55 Hence, CAT-3 with a content of 62.82 wt % of alumina will be the catalyst with the highest amount of acidic sites. Additionally, noticeable amounts of rare earths can be found in equilibrated FCC catalysts.…”
Section: Methodsmentioning
confidence: 99%
“…The content of alumina (Al 2 O 3 ) shown in Table S2 corresponds to total alumina, i.e., active and inactive alumina, as it can be found both in the HY zeolite and in the matrix. Its content gives an idea of the total amount of Al 3+ species, which can be directly correlated with Brønsted-type acidic sites . Hence, CAT-3 with a content of 62.82 wt % of alumina will be the catalyst with the highest amount of acidic sites.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, strong acidic sites are needed to initiate the cracking process, and special characters of pore structures are needed to limit the coke formation . The activity of zeolite in the cracking process is dependent on Brønsted acidic sites because the cracking reaction of hydrocarbons is carried out via formation of carbaniun ion intermediate. ,,, Also, the zeolites are widely used in hydrocarbon isomerization, hydrocracking, reforming, and alkylation processes as heterogeneous catalysts …”
Section: Introductionmentioning
confidence: 99%